2017
DOI: 10.1155/2017/4296075
|View full text |Cite
|
Sign up to set email alerts
|

Therapeutic Potentials of Synapses after Traumatic Brain Injury: A Comprehensive Review

Abstract: Massive studies have focused on the understanding of the pathobiology of cellular and molecular changes and injury mechanisms after traumatic brain injury (TBI), but very few studies have specially discussed the role of synapses in the context of TBI. This paper specifically highlights the role and therapeutic potentials of synapses after TBI. First, we review and conclude how synapses interact with constant structural, metabolic, neuroendocrine, and inflammatory mechanisms after TBI. Second, we briefly descri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 81 publications
(82 reference statements)
0
4
0
1
Order By: Relevance
“…It is likely that a local inflammatory synaptic loss, as well as neurodegeneration, might contribute to behavioral defects. Although the severity and duration of TBI may result in various synaptic changes [ 73 ], we did intend to further examine the synaptic loss at 1 month in our future study based on the reported phagocytic activity of microglia and astrocytes to synapses at 1 month [ 61 , 74 ].…”
Section: Discussionmentioning
confidence: 99%
“…It is likely that a local inflammatory synaptic loss, as well as neurodegeneration, might contribute to behavioral defects. Although the severity and duration of TBI may result in various synaptic changes [ 73 ], we did intend to further examine the synaptic loss at 1 month in our future study based on the reported phagocytic activity of microglia and astrocytes to synapses at 1 month [ 61 , 74 ].…”
Section: Discussionmentioning
confidence: 99%
“…Alterations in synaptic markers in hippocampus and cortex have been demonstrated in several animal models of TBI (Rachmany et al, 2017; Merlo et al, 2014; Ansari et al, 2008; Przekwas et al, 2016; Joo et al, 2018) as well as in AD, in both preclinical and clinical studies (Cambon et al, 2000; Heinonen et al, 1995; Selkoe, 2002; Berezcki et al, 2016). TBI, in particular, has been reported to acutely induce extensive dendritic de-arborization and a reduction in synapse number (Winston et al, 2013; Wen et al, 2017). Such a decline in synaptic strength has been proposed to underpin, at least in part, TBI mediated impairments in LTP and cognition (Liu et al, 2017).…”
Section: Discussionmentioning
confidence: 99%
“…Травма спинного мозку є складним інвалідизуючим ураженням, механізми якого нині далекі до вичерпного розуміння. У випадку травми головного мозку, за винятком незворотного ураження життєво важливих регуляторних центрів, втрачені функції компенсуються шляхом пластичних перебудов власних нейрональних мереж [1,2]. При травмі периферичних нервів відновлення втрачених функцій здійснюється шляхом проростання перетнутих волокон через зону ушкодження [3], а також за допомогою компенсаторної перебудови нейрональних мереж на рівні передусім головного мозку [4].…”
Section: вступunclassified